2017
DOI: 10.1021/acs.jpca.7b05030
|View full text |Cite
|
Sign up to set email alerts
|

5-Methylhydantoin: From Isolated Molecules in a Low-Temperature Argon Matrix to Solid State Polymorphs Characterization

Abstract: The molecular structure, vibrational spectra and photochemistry of 5-methylhydantoin (CHNO; 5-MH) were studied by matrix isolation infrared spectroscopy and theoretical calculations at the DFT(B3LYP)/6-311++G(d,p) theory level. The natural bond orbital (NBO) analysis approach was used to study in detail the electronic structure of the minimum energy structure of 5-MH, namely the specific characteristics of the σ and π electronic systems of the molecule and the stabilizing orbital interactions. UV irradiation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 33 publications
(61 reference statements)
2
17
0
Order By: Relevance
“…Following also the trend already noticed before for the parent hydantoin and both 1-methyl and 5-methyl hydantoins, [2][3][4] the ring internal angles with a nitrogen atom in the apex (C4-N3-C2 and C5-N1-C2) are much larger (around 113º) than those with carbon atoms in the apex (N1-C2-C3, N1-C5-C4 and N3-C4-C5; ~102-106º), pointing to relatively different s vs. p composition of the hybrid orbitals of the N and C atoms used to make the ring bonds.…”
Section: Conformational Landscape Of 5aah and Molecular Geometrysupporting
confidence: 83%
See 2 more Smart Citations
“…Following also the trend already noticed before for the parent hydantoin and both 1-methyl and 5-methyl hydantoins, [2][3][4] the ring internal angles with a nitrogen atom in the apex (C4-N3-C2 and C5-N1-C2) are much larger (around 113º) than those with carbon atoms in the apex (N1-C2-C3, N1-C5-C4 and N3-C4-C5; ~102-106º), pointing to relatively different s vs. p composition of the hybrid orbitals of the N and C atoms used to make the ring bonds.…”
Section: Conformational Landscape Of 5aah and Molecular Geometrysupporting
confidence: 83%
“…The most intense band is ascribable to the anti-symmetric ring carbonyl stretching vibration (n(C=O)as), being observed at 1768 (calculated, 1775 cm -1 ). As reported before for the parent hydantoin and its 1-methyl and 5-methyl substituted derivatives [2][3][4] this band has a satellite band at ~1753 cm -1 (appearing as a shoulder of the main band) which shall be assigned to the first overtone of the n(C11-C14) vibration (whose fundamental appears at 889/886 cm -1 ) enhanced by Fermi resonance interaction with n(C=O)as. The symmetric ring carbonyl stretching vibration (n(C=O)s) is observed at 1810 cm -1 (calculated at 1817 cm -1 ), while the substituent n(C14=O) carbonyl stretching mode gives rise to the band observed at 1752 cm -1 (calculated 1775 cm -1 ) which appears also overlapped with the most intense band due to n(C=O)as.…”
Section: Ir Spectrum Of Matrix-isolated 5aahsupporting
confidence: 57%
See 1 more Smart Citation
“…For deeper insight into the hydrogen-bonding effect on the polymorphic states and isomerization we applied a wide variety of research methods (DFT, X-ray, DSC, NQR, IINS, IR and Raman) in different environments and over a wide temperature range. It is worth noting that the method of matrix isolation was unique in its ability to trace metastable states and help interpret complex reactions [ 11 , 12 , 13 , 14 ]. Moreover, investigations of objects with hydrogen bonding by IINS [ 15 , 16 , 17 , 18 ] and NQR [ 19 , 20 ] techniques are useful.…”
Section: Introductionmentioning
confidence: 99%
“…Within the scope of our research programme on hydantoin derivatives [19][20][21][22][23][24], we have recently shown that 5AAH exhibits five different polymorphs, from which the most stable one at room temperature (polymorph I) has the peculiar characteristic of being formed by 5AAH molecules that assume a conformation identical to the highest-energy conformer for the isolated molecule [24]. In fact, this higher-energy conformer, which has an energy as large as ~40 kJ mol -1 higher than that of the conformational ground state, is selected upon crystallization from among 13 different conformers of the molecule.…”
Section: Introductionmentioning
confidence: 99%